STRATEGI RUSIA DALAM MEMPERTAHANKAN PEREKONOMIANNYA PASCA SANKSI AMERIKA SERIKAT 2014 - Fadila Azzahra Azzahra; Umi Oktyari Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Relations between Russia and the United States in the international world are inseparable from compitition with each other. Russia’s annexation of Crimea in 2014 le to the imposition of economic sanctions bye the United States. The studies how the strategy used by Russia in overcoming sanctions and results. The answer the statement, the authors use the theory of international coorperation by K.J Holsti as a references, as well as the writing technique used in this scientific work uses library research and data analysis method. Russia cooperates withcountries n the Middle Esat in the nuclear sector. Russia allies to China, and strengthened ties with each other, thereby making China as the future of Russia. This strategy succeeded preventing humans from an economic downturn, this was marked by more intense cooperation between China and Russia with an increase the number of Russian imports to China. Keywords: Nuclear energy, bilateral relations, economic santions.